Higher immunoglobulin A nephropathy recurrence in related‐donor kidney transplants: The Japan Academic Consortium of Kidney Transplantation study. (21st July 2019) - Okumi, Masayoshi; Okada, Daigo; Unagami, Kohei; Kakuta, Yoichi; Iizuka, Junpei; Takagi, Toshio; Shirakawa, Hiroki; Omoto, Kazuya; Ishida, Hideki; Tanabe, Kazunari; ,
Abstract : Objective: To investigate the 10‐year biopsy‐proven recurrence rates and risk factors for immunoglobulin A nephropathy recurrence in kidney transplant recipients. Methods: We included 299 kidney transplant recipients from 1995 to 2015, who had biopsy‐proven underlying immunoglobulin A nephropathy and underwent zero‐hour biopsy. The primary end‐point was recurrence of immunoglobulin A nephropathy. We compared clinical, treatment and graft failure among those with and without recurrent immunoglobulin A nephropathy. A time‐to‐recurrence analysis was carried out using the competing risk analysis and time‐dependent Cox model. Results: Of 299 recipients, 80 had recurrent immunoglobulin A nephropathy (66.3% with clinical biopsy and 33.7% with protocol biopsy, post‐transplant biopsy rate: 90.6%). The 10‐year recurrence rate was 34.3% (95% confidence interval 27.6–41.1). Related‐donor transplantation (hazard ratio 2.28, P = 0.009) and post‐transplant increased proteinuria (hazard ratio 1.59, P < 0.001) were identified as potential risk factors for immunoglobulin A nephropathy recurrence. The 10‐year rates were 41.5% in related donor recipients and 16.3% in unrelated donor recipients. There was no conclusive evidence that the calcineurin inhibitor, antimetabolites, basiliximab and rituximab reduce immunoglobulin A nephropathy recurrence. Immunoglobulin A nephropathy recurrence was associated with an increased risk of death‐censored graft failure (hazard ratio 5.29, 95% confidence interval 1.39–20.17, P = 0.015). However, related donor itself was not associated with an increased risk of graft failure. Conclusions: The present results have clinical implications in that the signs of recurrent immunoglobulin A nephropathy should be evaluated carefully in recipients receiving related‐donor transplants. There is a need for further studies related to genetic and/or familial interactions in kidney transplant recipients with immunoglobulin A nephropathy and related donors.